Cassie Dewell : Paradise Valley - Book 4 - Box, C. J. (New York : Minotaur Books, 2017)
"For three years, Investigator Cassie Dewell has been on a hunt for a serial killer known as The Lizard King. He works as a long haul trucker. His prey are the "lot lizard" prostitutes who frequent truck stops. And she almost caught him...once. Working for the Bakken County, North Dakota sheriff's department, Cassie has set what she believes is the perfect trap and she has lured him and his truck to a depot. Standing by, ready to close the net are half a dozen undercover officers, including Cassie's fiance Ian. But the plan goes horribly wrong, and the blame falls to Cassie. Disgraced, she loses her job and investigation into her role is put into motion. At the same time, Kyle Westergaard, a troubled kid whom Cassie has taken under her wing, has disappeared, telling everyone he is going on a long-planned adventure. Kyle's grandmother begs Cassie to find him and with nothing else to do, she agrees--all the while planning a new trap for The Lizard King. But Cassie is now a lone wolf. And in the same way that two streams converge into a river, Kyle's disappearance may have a more sinister meaning than anyone realizes. With no allies, no support, and only her own wits to rely on, Cassie must take down a killer who is as ruthless as he is cunning. But can she do it alone, without losing her own humanity or her own life?"--
Publishers Weekly
Kirkus Reviews
Booklist
Library Journal
Adult
Keywords: Policewomen -- Fiction -- North Dakota; Mystery fiction; Mystery fiction; Suspense fiction